2012
DOI: 10.3390/ijms13089959
|View full text |Cite
|
Sign up to set email alerts
|

Chick Chorioallantoic Membrane (CAM) Assay as an In Vivo Model to Study the Effect of Newly Identified Molecules on Ovarian Cancer Invasion and Metastasis

Abstract: The majority of ovarian cancer patients present with advanced disease and despite aggressive treatment, prognosis remains poor. Significant improvement in ovarian cancer survival will require the development of more effective molecularly targeted therapeutics. Commonly, mouse models are used for the in vivo assessment of potential new therapeutic targets in ovarian cancer. However, animal models are costly and time consuming. Other models, such as the chick embryo chorioallantoic membrane (CAM) assay, are ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
257
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(265 citation statements)
references
References 34 publications
4
257
1
3
Order By: Relevance
“…It is reported that the CAM model is a widely used in vivo model for determining the progress of angiogenesis (45). Angiogenesis is the formation of new blood vessels, and therefore, it is a vital process required for both physiological and pathological conditions (46).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the CAM model is a widely used in vivo model for determining the progress of angiogenesis (45). Angiogenesis is the formation of new blood vessels, and therefore, it is a vital process required for both physiological and pathological conditions (46).…”
Section: Discussionmentioning
confidence: 99%
“…For topical administration, the compound is applied on the CAM surface. This route is the most commonly used one, owing to the accessibility to the CAM by simply opening the eggshell/adhesive film 22,23 . Although IV administration is feasible, the difficulty to insert needles into the CAM vessels is a critical limitation.…”
Section: Time Of Inoculation and Harvestmentioning
confidence: 99%
“…The eggs were property sealed again by using cellophane tape and kept it back to the incubator and they were incubated undisturbed till day 14. On the 14 th day of incubation, the eggs were taken out from the incubator and the CAM tissues directly beneath each filter paper was resected with the help of forceps 15 . The anti-angiogenic effect of the test drugs was quantified by comparing the quantity of blood capillaries mainly under the area of the disk (where the drug was loaded) by capturing the images before and after treatment.…”
Section: Chick Chorioallantoic Membrane Assaymentioning
confidence: 99%